Inactivation of aerosolized Bacillus anthracis surrogate spores in close proximity to the flame: Simulation study. (February 2019) - Nakpan, Worrawit; Yermakov, Michael; Indugula, Reshmi; Jandarov, Roman; Reponen, Tiina; Grinshpun, Sergey A.
Abstract: Survival of bio-warfare aerosol agents exposed to different environmental conditions has gained substantial attention in the biodefense and biosecurity research communities. The present simulation study aimed at investigating the survival of aerosolized bacterial spores in close proximity to a flame under test conditions relevant to a fire or explosion in a bio-weapon facility. The tests were conducted with aerosolized spores of Bacillus thuringiensis var. kurstaki (Btk), a well-recognized surrogate of Bacillus anthracis, which is a common bio-warfare agent. The loss in spore viability resulting from their exposure to a peripheral area of an air-acetylene flame at two particle-to-flame proximity levels was experimentally determined for different exposure time intervals ranging approximately from 0.1 to 6.0 s. The spore inactivation was quantified through comparison of the viability levels obtained for exposed and non-exposed (control) samples. At relatively short time intervals, the inactivation rate was close to exponential. However, as the exposure time increased, the spore viability decrease slowed down for both proximity levels. The "breaking point" was found to be dependent on the particle-to-flame proximity. The findings point to a small fraction of spores that exhibits particularly high resistance to the stress from the flame-originated heat. To verify the existence of such a sub-population, a separate experiment was performed, in which the aerosolized spores that survived the stress caused by exposure to flame were subsequently subjected to an additional (post-exposure) stress by being placed in an oven for 5, 10 and 20 s. The study results demonstrated the presence of "super-resistant" Btk spores. This justifies the need of developing special materials with pronounced biocidal capabilities (well in excess of those associated with an air-acetylene flame) in order to effectively inactivate "super-resistant" aerosolized bio-agents. Highlights: Exposure of an aerosolized bio-agent to fire in a bio-weapon facility was simulated. A fraction of Btk spores super-resistant to flame-generated heat was identified. Spores survived the pre-flame exposure develop extra heat stress resistance.